CFD modeling of flow and local scour around submerged bridge decks - Fleit, Gábor; Baranya, Sándor; Ehlers, Ronja; Bihs, Hans (Journal of Coastal and Hydraulic Structures, 2023)
In this study, the level set method-based, multiphase hydro- and morphodynamic numerical model REEF3D is used for the simulation of the flow conditions and local scouring around submerged bridge decks. Presence of hydraulic jumps, bridge overtopping, pressurized jets and the resulting scouring make the selected test cases especially challenging from the numerical modelling point of view. The models are validated against data from laboratory experiments. The influence of the submergence ratio on the prevailing flow and scouring is investigated. The level set method showed robustness and good accuracy for the treatment of the complex free surface as well as for the tracking of the mobile bed. The submergence ratio showed no clear correlation with the prevailing erosion/deposition patterns. As the simulations offered insights into the prevailing hydrodynamics and thus the relevance of numerical modelling was emphasized for such complex sediment transport problems.